2012
DOI: 10.1111/j.1460-6984.2011.00092.x
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic transfer in bilingual children with specific language impairment

Abstract: It is concluded that children's formal linguistic skills in L1 and L2 tend to be related and that their level of L1 proficiency may help to develop linguistic skills in L2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 26 publications
2
24
4
Order By: Relevance
“…For example, Blom and Paradis (2015) documented an average difference of 30% in production accuracy between children with TD and LI for 5-to 7-year-olds who had been learning English for about 3.5 years on average. Verhoeven, Steenge, and van Balkom (2012) documented similar patterns of performance on verb tense marking for children acquiring Dutch as a second language. These findings confirm the difficulty bilingual children with LI have with tense marking as documented for monolingual English speakers.…”
Section: Grammatical Challenges Of Ells With Td and LImentioning
confidence: 63%
“…For example, Blom and Paradis (2015) documented an average difference of 30% in production accuracy between children with TD and LI for 5-to 7-year-olds who had been learning English for about 3.5 years on average. Verhoeven, Steenge, and van Balkom (2012) documented similar patterns of performance on verb tense marking for children acquiring Dutch as a second language. These findings confirm the difficulty bilingual children with LI have with tense marking as documented for monolingual English speakers.…”
Section: Grammatical Challenges Of Ells With Td and LImentioning
confidence: 63%
“…This early shift in dominance may be another reflection of L1 attrition in this sample. In contrast, sequential bilingual children with PLI in the Netherlands (Verhoeven et al, 2012) showed relative dominance in L1.…”
Section: Discussionmentioning
confidence: 95%
“…This task served as a measure of lexical retrieval and was also taken from the Standardized Screening Test for Children with Specific Language Impairment (Verhoeven, 2006; Cronbach’s alpha = 0.95). We used the picture naming task in which participants are asked to name pictures in a serial naming task.…”
Section: Methodsmentioning
confidence: 99%